Antarctic petrels ‘on the ice rocks’: wintering strategy of an Antarctic seabird - Delord, Karine; Kato, Akiko; Tarroux, Arnaud; Orgeret, Florian; Cotté, Cedric; Ropert-Coudert, Yan; Cherel, Yves; Descamps, Sébastien (Royal Society Open Science, 2020)
There is a paucity of information on the foraging ecology, especially individual use of sea-ice features and icebergs, over the non-breeding season in many seabird species. Using geolocators and stable isotopes, we defined the movements, distribution and diet of adult Antarctic petrels Thalassoica antarctica from the largest known breeding colony, the inland Svarthamaren, Antarctica. More specifically, we examined how sea-ice concentration and free-drifting icebergs affect the distribution of Antarctic petrels. After breeding, birds moved north to the marginal ice zone (MIZ) in the Weddell sector of the Southern Ocean, following its northward extension during freeze-up in April, and they wintered there in April–August. There, the birds stayed predominantly out of the water (60–80% of the time) suggesting they use icebergs as platforms to stand on and/or to rest. Feather δ15N values encompassed one full trophic level, indicating that birds fed on various proportions of crustaceans and fish/squid, most likely Antarctic krill Euphausia superba and the myctophid fish Electrona antarctica and/or the squid Psychroteuthis glacialis. Birds showed strong affinity for the open waters of the northern boundary of the MIZ, an important iceberg transit area, which offers roosting opportunities and rich prey fields. The strong association of Antarctic petrels with sea-ice cycle and icebergs suggests the species can serve, year-round, as a sentinel of environmental changes for this remote region.
Keywords: Sørishavet; Weddellhavet; biologi; geolokalisering; havis; isberg; isfjell; klimaendringer; miljøendringer; ornitologi; petreller; sjøfugler; sjøis; økologi

Spring phenology shapes the spatial foraging behavior of Antarctic petrels - Fauchald, Per; Tarroux, Arnaud; Tveraa, Torkild; Cherel, Yves; Ropert-Coudert, Yan; Kato, Akiko; Love, Oliver P; Varpe, Øystein; Descamps, Sébastien (Marine Ecology Progress Series, 2017)
In polar seas, the seasonal melting of ice triggers the development of an open-waterecosystem characterized by short-lived algal blooms, the grazing and development of zooplank-ton, and the influx of avian and mammalian predators. Spatial heterogeneity in the timing of icemelt generates temporal variability in the development of these events across the habitat, offeringa natural framework to assess how foraging marine predators respond to the spring phenology.We combined 4 yr of tracking data of Antarctic petrels Thalassoica antarcticawith synopticremote-sensing data on sea ice and chlorophyll ato test how the development of melting ice andprimary production drive Antarctic petrel foraging. Cross-correlation analyses of first-passagetime revealed that Antarctic petrels utilized foraging areas with a spatial scale of 300 km. Theseareas changed position or disappeared within 10 to 30 d and showed no spatial consistency amongyears. Generalized additive model (GAM) analyses suggested that the presence of foraging areaswas related to the time since ice melt. Antarctic petrels concentrated their search effort in meltingareas and in areas that had reached an age of 50 to 60 d from the date of ice melt. We found nosignificant relationship between search effort and chlorophyll aconcentration. We suggest thatthese foraging patterns were related to the vertical distribution and profitability of the main prey,the Antarctic krill Euphausia superba. Our study demonstrates that the annual ice melt in theSouthern Ocean shapes the development of a highly patchy and elusive food web, underscoringthe importance of flexible foraging strategies among top predators. KEY WORDS: Area-restricted search · Euphausia superba· Marginal ice zone · Phytoplanktonbiomass · Procellariiformes · Sea ice dynamics · Southern Ocean · Thalassoica antarctica
Keywords: Sørishavet; Weddellhavet; biologi; biomasse; fenologi; fytoplankton; fôring; havis; klima; petreller; sjøis; smelting; økosystemer

The retrospective analysis of Antarctic tracking data project - Ropert-Coudert, Yan; Van de Putte, Anton P; Reisinger, Ryan R; Bornemann, Horst; Charrassin, Jean-Benoît; Costa, Daniel P; Danis, Bruno; Hückstädt, Luis A; Jonsen, Ian D; Lea, Mary-Anne; Thompson, David; Torres, Leigh G; et al. (Scientific Data, 2020)
The Retrospective Analysis of Antarctic Tracking Data (RAATD) is a Scientific Committee for Antarctic Research project led jointly by the Expert Groups on Birds and Marine Mammals and Antarctic Biodiversity Informatics, and endorsed by the Commission for the Conservation of Antarctic Marine Living Resources. RAATD consolidated tracking data for multiple species of Antarctic meso- and top-predators to identify Areas of Ecological Significance. These datasets and accompanying syntheses provide a greater understanding of fundamental ecosystem processes in the Southern Ocean, support modelling of predator distributions under future climate scenarios and create inputs that can be incorporated into decision making processes by management authorities. In this data paper, we present the compiled tracking data from research groups that have worked in the Antarctic since the 1990s. The data are publicly available through biodiversity.aq and the Ocean Biogeographic Information System. The archive includes tracking data from over 70 contributors across 12 national Antarctic programs, and includes data from 17 predator species, 4060 individual animals, and over 2.9 million observed locations.
Keywords: Antarktis; Sørishavet; biologi; økologi; økosystem